Conflict mediation, an undisclosed skill among medical students: a review - Ortega Villa, Esmeralda (2022)
Human beings are social beings by nature, and disagreements and conflicts are common situations inherent in their different social activities. This review aims to describe the origin of conflicts and the mediation techniques in healthcare. It is well known that conflict resolution skills are needed to be learned, and such skills are considered within the changing priorities of healthcare students. Disagreement and conflict are inevitable between members of clinical care teams, as well as with patients and their families during healthcare. Despite the importance of these skills, they have not been established as an educational need in healthcare professionals’ curricula, even though physicians are required to negotiate and resolve conflicts on an ongoing basis in healthcare settings. Our role as educators is to analyze the changing empirical professional context, and provide our students with the relevant tools with the greatest chance of success for their professional development in their daily activities. We invite you to read, analyze and criticize this proposal, which we consider very important to be included in the undergraduate and graduate curricula of the different fields of healthcare professionals, i.e. specialist physicians, nursing staff and all those professionals who work with the common goal of providing quality healthcare.